On Rotating Positions in Archaeology, Art, and Architecture: ’Grindbakken’ - Liefooghe, Maarten (Journal of Contemporary Archaeology, 2018)
This article questions the usefulness of new container labels like ‘creative archaeology’ to denominate practices beyond more traditional understandings of art or archaeology. Such new labels risk to smooth out the differences between practices that take different positions in one of the many possible interfaces between art and archaeology. Terminology that does not provoke resistance because it masks disciplinary differences is less interesting than a variegated discourse that allows to reflect critically on the different epistemic and aesthetic stakes and merits among ‘creative practices’ in art/archaeology and that can help to make these practices reflexive. A case is made for acknowledging the professional mobility of disciplinary attitudes while retaining the critical frameworks of distinct disciplinary fields. Such mobility is explored in the case of the in situ Grindbakken exhibition by Belgian architecture collective Rotor.